Clinoenstatite/Tantalum Coating for Enhancement of Biocompatibility and Corrosion Protection of Mg Alloy - Hamid Reza Bakhsheshi-Rad; Aliakbar Najafinezhad; Esah Hamzah; Ahmad Fauzi Ismail; Filippo Berto; Xiongbiao Chen (Journal of Functional Biomaterials, 2020)
Biodegradable Mg alloys have appeared as the most appealing metals for biomedical applications, particularly as temporary bone implants. However, issues regarding high corrosion rate and biocompatibility restrict their application. Hence, in the present work, nanostructured clinoenstatite (CLT, MgSiO3)/tantalum nitride (TaN) was deposited on the Mg-Ca-Zn alloy via electrophoretic deposition (EPD) along with physical vapor deposition (PVD) to improve the corrosion and biological characteristics of the Mg-Ca-Zn alloy. The TaN intermediate layer with bubble like morphology possessed a compact and homogenous structure with a thickness of about 950 nm while the thick CLT over-layer (~15 μm) displayed a less compact structure containing nano-porosities as well as nanoparticles with spherical morphology. The electrochemical tests demonstrated that the as prepared CLT/TaN film is able to substantially increase the anticorrosion property of Mg-Ca-Zn bare alloy. Cytocompatibility outcomes indicated that formation of CLT and TaN on the Mg bare alloy surface enhanced cell viability, proliferation and growth, implying excellent biocompatibility. Taken together, the CLT/TaN coating exhibits appropriate characteristic including anticorrosion property and biocompatibility in order to employ in biomedical files.